Improving resilience to hot weather in the UK: The role of communication, behaviour and social insights in policy interventions. Issue 94 (April 2019) - Howarth, Candice; Kantenbacher, Joe; Guida, Kristen; Roberts, Tom; Rohse, Mel
Highlights: Social, communication and behaviour insights must be incorporated into hot weather policies. Resilience can be improved with consideration of international and cross-sector best practice. Social processes can limit or enhance climate resilience measures. Abstract: At present, there is little guidance on how to communicate the dangers relating to hot weather events and on how to better prepare for them. Social responses to hot weather risks need to be a priority as populations around the world become more exposed to these under a changing climate. In this commentary, we argue that policy interventions focused on improving resilience to hot weather need to be more closely aligned with broader sustainability challenges and more effectively incorporate communication, behaviour, and social insights. With a particular focus on the UK, we highlight the risks of not taking these into account and outline ways in which policy-making on hot weather events could be improved, by drawing on international best practice and supporting decision-making within a range of relevant institutions across the health, transport and housing sectors.